The narrative of ethnic minority children on education in Central Java – Indonesia - Sulistyani, Hapsari Dwiningtyas; Rahardjo, Turnomo; Rahmiaji, Lintang Ratri; Suprihatini, Taufik (Penerbit Universiti Kebangsaan Malaysia, 2020)
Education is a significant narrative to develop society. Any developmental effort that targets local people should take into account the local education system in place, which has been passed on from one generation to another. Comprehending local children's narratives on education is crucial for formulating an education method that incorporates both formal educational principals and local educational practices. The central locus of this research is to explore how the children of Sikep -- an ethnic minority group in Indonesia that has a specific perspective on education and social values -- give meaning to the discourse of education. There are six informants in this study. They are Sikep children from Baturejo Village, Pati Regency, Indonesia. The research used in the study is an ethnographic approach made by employing qualitative interviews and observing the life of the Sikep community. The findings signify that the Sikep children have a specific narrative on education. Such narratives determine their interpretation of the education process in their daily lives. There are specific principles of learning held by the Sikep children such as the parents are the main teachers, learning agricultural works in their daily lives as a part of the hard-skills requirement, and practicing local values of morality and spirituality as soft skills. The narrative of the Sikep children on education suggests that school as a learning process in their daily lives cannot be replaced by the formal school. Hence, the education process which accommodates the local values is necessary to increase the Sikep children’s participation in formal school.